The Genetic Etiology Diagnosis of Fetal Growth Restriction Using Single-Nucleotide Polymorphism-Based Chromosomal Microarray Analysis - Chen, Yu'e; Xie, Yingjun; Jiang, Yuying; Luo, Qi; Shi, Lijing; Zeng, Shuhong; Zhuang, Jianlong; Lyu, Guorong (Frontiers in Pediatrics, 2021)
Background: An increasing of pathogenic copy number variants (pCNVs) has been recognizing to associate with fetal growth restriction (FGR). Here, we aim to explore the application value of chromosomal microarray analysis (CMA) in prenatal diagnosis of FGR. Methods: Prenatal ultrasound was employ to identify FGR. A total of 149 pregnancy women with FGR were enrolled in our study. All subjects underwent karyotyping and CMA to reveal the chromosome abnormalities. Results: In this study, all subjects were successfully detected by karyotying and CMA analysis. Of these subjects, the chromosome abnormalities detection rate were 5.37% (8/149) and 13.42% (20/149) for karyotyping and CMA, respectively. Among them, an 8.05% (12/149) incremental yield of CMA over karyotyping was observed (P=0.004). In addition, a significant difference of pCNVs detection rate was observed between the groups with different high-risk factors (P=0.005). The FGR with structural anomalies group showed the highest pCNVs detection rate (33.33%), followed by FGR with non-structural anomalies group (8.77%) and isolated FGR group (8.06%). Conclusion: In conclusion, CMA technology showed an effective application value in etiology diagnosis of FGR, we believe that CMA should be recommended as first line detection technology for prenatal diagnosis in FGR.